Komodifikasi Adzan Magrib Ramadan Kartun Upin-Ipin di MNC TV - Wibowo, Ganjar; Saefuddin, Bunnaya (Universitas Al Azhar Indonesia, 2022)
Through the media political economy approach, this study reveals how the commodification performed on impressions insertion Adzan Maghrib animation Upin Ipin in the month of Ramadan which took place in Station Media Nusantara Citra Televisi (MNCTV) Jakarta. The results showed that the commodification shows inset Adzan Maghrib Ramadan took place behind the ideology of the political economy of the media. Commodification of the Adzan Maghrib Ramadan Upin-Ipin animation study of content, workers and audiences. Outside Ramadan Adzan Maghrib a regular insertion program but during Ramadan maghrib call to prayer was turned into a privileged, by the media workers trafficked profit even doubled. This study uses a critical paradigm with a qualitative approach. In the process of commodification of the Adhan maghrib animation Upin-Ipin Ramadan the practice of trade transactions and multiple profits involving elements, content of workers and the audience.